2019
DOI: 10.1016/j.str.2019.05.002
|View full text |Cite
|
Sign up to set email alerts
|

A Conserved Allosteric Pathway in Tyrosine Kinase Regulation

Abstract: Highlights d There is an allosteric pathway between the DFG motif and the molecular brake d An isoleucine near the DFG motif serves as a conduit of allostery d Pathological mutations at the molecular brake perturb the allosteric network d Molecular brake mutants decrease kinase thermal stability

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 31 publications
0
11
0
Order By: Relevance
“…Indeed, both computational and experimental methods have successfully elucidated allosteric pathways in a variety of different systems outside of protein kinase A 45 52 . Perhaps more importantly, many of these studies have shown how disruptions in these pathways act to change function.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, both computational and experimental methods have successfully elucidated allosteric pathways in a variety of different systems outside of protein kinase A 45 52 . Perhaps more importantly, many of these studies have shown how disruptions in these pathways act to change function.…”
Section: Discussionmentioning
confidence: 99%
“…Highly coupled motions between distant sites of KIT, as evidenced by the cross-correlation maps, suggests its association with the functional dependence of these regions, which is classified as allosteric regulation, the phenomenon largely observed in many proteins [2,3,53,54]. In particular, the coupling motions in each lobe, N-and C-lobe, of the TK domain and between the lobes reflect the allosteric regulation of the kinase function, which is well-described for different non-receptor and receptor tyrosine kinases [3,55,56]. The coupled motions of two activating regions of KIT, A-loop, and JMR were characterized, in terms of their allosteric communication in the wild-type KIT, which was disrupted in oncogenic mutants [40,57].…”
Section: Discussionmentioning
confidence: 75%
“…On the side of practical implications and from the perspective of the recently emerged paradigm of precision medicine, , allosteric ligands act as modulators ,, that induce noncompetitive and tunable allosteric regulation of protein activity, rendering them attractive in drug design. Specifically, allosteric drugs allow one to circumvent the side effects typical for orthosteric medicines aiming at the highly conserved orthosteric sites in two major drug targets, kinases and G protein-coupled receptors (GPCRs): (i) off-target toxicity caused by interactions with other kinases; , (ii) consequences of desensitization and internalization of GPCRs, ,,,, via binding to distal allosteric sites which are less conserved, thereby providing high selectivity and being less prone to inducing receptor desensitization/internalization compared to orthosteric drugs, respectively.…”
Section: Introductionmentioning
confidence: 99%